2015
DOI: 10.1111/ffe.12309
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network approach to predict the fracture parameters of the size effect model for concrete

Abstract: The fracture parameters (the fracture energy and the effective length of the fracture process zone for an infinitely large specimen) in the size effect model of concrete exhibit a large scatter as measured in most of the experimental studies. This phenomenon is ubiquitous and has presented a great challenge to characterize the structural failure over the last decade. In order to remove the perplexing issue, this paper develops two models to predict the two fracture parameters using the artificial neural networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The complex constitution of concrete results in the sophisticated damage experience in the material under loading. Specifically, the arbitrary distribution of numerous initial defects in the material causes the localization of stresses, and the localized stresses produce the complex process of damage in an increasingly complicated way during load process. Additionally, experimental studies had been conducted to understand the damage mechanism in concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The complex constitution of concrete results in the sophisticated damage experience in the material under loading. Specifically, the arbitrary distribution of numerous initial defects in the material causes the localization of stresses, and the localized stresses produce the complex process of damage in an increasingly complicated way during load process. Additionally, experimental studies had been conducted to understand the damage mechanism in concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous studies [ 28 , 37 ], one hidden layer is applied due to the limited input and output variables. The network with too many hidden layers or neurons can be easily over-trained and will not sufficiently predict the new data.…”
Section: Methodsmentioning
confidence: 99%
“…Yan et al [ 28 ] reported the following formulation to estimate the neuron number in the single hidden layer: where , and the neuron numbers of hidden, input and output layers, respectively. is a constant, ranging from 1 to 10.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these studies on various concrete types are as follows. Yan et al [1] presumed the fracture parameters of the size effect model for concrete, Chen et al [2] predicted the concrete properties, Wang et al [3] estimated the expansion behavior of self-stressing concrete, Imam et al [4] modeled residual strength of corroded reinforced concrete Beams. Kostic and Vasovic [5] built a model for compressive strength of basic concrete.…”
Section: Introductionmentioning
confidence: 99%